2014
DOI: 10.3390/molecules19068140
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Fungicidal Activity of Novel Chloro-Containing 1-Aryl-3-oxypyrazoles with an Oximino Ester or Oximino Amide Moiety

Abstract: Six novel chloro-containing 1-aryl-3-oxypyrazoles TMa-TMf with an oximino ester or an oximino amide moiety were prepared by the reaction of 1-aryl-1H-pyrazol-3-ols with benzyl bromide. Their structures were characterized by 1 H-NMR, 13 C-NMR, IR, MS, and elemental analysis. A preliminary in vitro bioassay indicated that compounds TMa, TMe and TMf displayed excellent fungicidal activity against Rhizoctonia solani and could be used as potential lead compounds for further development of novel fungicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Intermediates N -arylpyrazoles I were synthesized from arylhydrazines via addition-cyclization and oxidation, which could then afford 4-bromo- N -arylpyrazoles IV by bromination 17 . Intermediate benzyl bromide ( E )-methyl 2-(2-(bromomethyl)phenyl)-2-(methoxyimino)acetate II was prepared from 1-( o -tolyl)ethanone via four steps including oxidation, esterification, oximation and bromination 8 . A previous report by Kim et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermediates N -arylpyrazoles I were synthesized from arylhydrazines via addition-cyclization and oxidation, which could then afford 4-bromo- N -arylpyrazoles IV by bromination 17 . Intermediate benzyl bromide ( E )-methyl 2-(2-(bromomethyl)phenyl)-2-(methoxyimino)acetate II was prepared from 1-( o -tolyl)ethanone via four steps including oxidation, esterification, oximation and bromination 8 . A previous report by Kim et al .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, several strobilurin analogues ( 4a-4f , 5a-5h , 6a-6h , Fig. 1 ) have been prepared by the substitution of N -arylpyrazoles with benzyl bromide in acetone, using potassium carbonate (K 2 CO 3 ) as acid-binding agent 7 , 8 . Motivated by this reaction, in our procedure, N -arylpyrazoles IV and I were allowed to react with benzyl bromide II and III , respectively, in a molar 1:1.1 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were screened for their antifungal and antibacterial activity as well and found almost equipotent to that of standard [42]. Liu et al [43] synthesized novel chloro containing 1-aryl-3oxypyrazoles derivatives and confirmed them with various spectroscopic techniques. They also screened these compounds against Rhizoctonia solani and found these compounds to be active.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…The pyrazolones, an important class of heterocyclic compounds, are prevalent in a wide range of bioactive compounds with pharmaceutical and agricultural activities. [1][2][3][4][5] 4-Iodopyrazole-3-ols could open the way to a quick access to many pyrazolone analogues. However, iodination is usually difficult owing to the low electrophilicity of iodide.…”
mentioning
confidence: 99%